Projections of Environmental Pollution in Ukraine - O. CHERENKEVYCH (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
The balanced environmentally sustainable economic development of Ukraine can be achieved by increasing the efficiency of the nature protection efforts, which requires the improved methods for assessment, modeling and forecasting of environmental performance and environmental pollution indicators. The article’s objective is to make a statistical forecasting of environmental pollution indicators in Ukraine, to outline the areas of nature protection work in this country. Air pollution, water pollution and hazardous wastes in Ukraine are forecasted considering the main factors of influence, selected with reference to the Strategy of the State Environmental Policy of Ukraine: GDP, the number of implemented resource-saving technologies, energy intensity of GDP, current spending on environmental protection. The project estimates for air pollution, water pollution and hazardous wastes were derived by use of regression models and factors projection. Results of the forecasting show that the emission of pollutants and carbon dioxide in the air, water pollution and pollution with hazardous wastes will be significantly reduced by 2022 if the current trends and patterns of development remain unchanged. Results of the forecasting confirm the need to introduce a series of measures concerned with waste treatment, air pollution and water pollution, to improve the regulatory system in nature protection activities in Ukraine.